Targeting terrorists: a license to kill? - Plaw, Avery (Ethics and global politics, 2008)
1. The issue of targeting terrorists -- 2. The development of Israel's terrorist targeting policy -- 3. The expansion of Israeli targeting during the second intifada -- 4. The development of the US terrorist targeting policy -- 5. The legality of targeting terrorists -- 6. The politics of targeting terrorists -- 7. The morality of targeting terrorists -- 8. Talking about targeting.